Revisiting the role of professionals in designing buildings with low embodied and operational energy - Tennakoon, G A; Waidyasekara, Anuradha; Ekanayake, B J (Built environment project and asset management, 2020)
PurposeMany studies have focused on embodied energy (EE) and operational energy (OE), but a shortage of studies on decision making, which involves several decision makers whose decisions can affect the energy performance of buildings, is evident. From the stages of the project life cycle, the design stage is identified as the ideal stage for integrating energy efficiency into buildings. Therefore, the purpose of this paper is to revisit the role of professionals in designing energy-conscious buildings with low EE and OE.Design/methodology/approachThis study administered a qualitative approach. Data were collected through semi-structured interviews only with 12 experts, due to the lack of expertise in the subject matter. The data were analyzed using manual content analysis.FindingsThe outcomes revealed the necessity to revisit the role of construction professionals in terms of adopting energy-efficient building design concepts from the project outset. The roles of the key professional groups (i.e. architects, structural engineers, services engineers and quantity surveyors) were identified through this research. Common issues in designing energy-efficient buildings and the means of addressing such problems were outlined.Originality/valueThis study contributes to the knowledge by revisiting the roles of construction professionals and proposing how they could leverage their strengths to play the important role and contribute collectively to design buildings with both low OE and EE.